2011
DOI: 10.1265/jjh.66.71
|View full text |Cite
|
Sign up to set email alerts
|

高齢者胃電図と心窩部温罨法の影響

Abstract: This increase in the translation error suggests that the electrical synergy between the stomach and intestine could be enhanced by the application of a hot stupe. Our findings also indicated that hot stupe application on the epigastrium was effective for improving gastrointestinal motility in elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…14 The diameter of the mesenteric artery was widened, blood flow increased, and intestinal peristalsis was accelerated by thermal stimulation (41°C) from heat transfer control device at the umbilicus. 47 It was also found that after hot stupe application on the epigastrium (40°C), gastroenterogram showed that the electrical synergy between the stomach and intestine was enhanced, stimulating the electrical rhythm and effectively improving gastrointestinal peristalsis, 48 indicating that the generation of local thermal stimulation can regulate gastrointestinal function. However, the differences between heating and moxibustion, particularly their relative impacts on gastrointestinal function, require further investigation.…”
Section: Gastrointestinal (Gi) Toxicitymentioning
confidence: 98%
“…14 The diameter of the mesenteric artery was widened, blood flow increased, and intestinal peristalsis was accelerated by thermal stimulation (41°C) from heat transfer control device at the umbilicus. 47 It was also found that after hot stupe application on the epigastrium (40°C), gastroenterogram showed that the electrical synergy between the stomach and intestine was enhanced, stimulating the electrical rhythm and effectively improving gastrointestinal peristalsis, 48 indicating that the generation of local thermal stimulation can regulate gastrointestinal function. However, the differences between heating and moxibustion, particularly their relative impacts on gastrointestinal function, require further investigation.…”
Section: Gastrointestinal (Gi) Toxicitymentioning
confidence: 98%